EVALUASI PELATIHAN PENINGKATAN KOMPETENSI PROFESIONAL GURU SEKOLAH MENENGAH PERTAMA - Sofyan Anif; Sutama Sutama; Harun Joko Prayitno; Sukartono Sukartono (Manajemen Pendidikan, 2020)
Improvement of teacher professional competency can be done through training. However, training has not been fully successful, therefore training activities need to be evaluated relating to training materials, instructor requirements, training facilities, training methods, and implementation process. The purpose of this study is to analyze and evaluate of training to improve the professional competence of junior high school teachers. This research uses a qualitative approach. Research subjects is education authorities, supervisors, principals, and junior high school teachers in Kendal Regency. Data collection techniques with a questionnaire; interviews, and documentation. Data analysis techniques using the flow method through the process of collecting, reducing, displaying, drawing and verifying data. The results of the study show that indicators of training materials have an average 2.12 (not good), instructor requirements 1.81 (not good), existence of training facilities 1.64 (not good), training methods 1.80 (not good), and management training conducted is on an average of 1.97 (not good). Based on these results it can be interpreted that the training has not been as expected and needs to be followed up with better management.